SERTIFIKAT BUKAN HAK MUTLAK DALAM KEPEMILIKAN TANAH Kajian Putusan No.1333/Pdt.G/2021/PN.Tng - Silooy, Ester; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
The independence of judges in examining and deciding a case reflects the characteristics of a legal state, but this independence sometimes needs to match what is expected. Seekers of justice initially had the enthusiasm to find a sense of justice in the judiciary, but the reality was far from expectations. Sometimes, professionals are disappointed with the background of the knowledge they study because it is contrary to reality. What is the evidentiary strength of the certificate as an authentic deed, and did the panel of judges consider the formal evidentiary aspects in handling case No.1333/Pdt.G/2021/PN?TNG is a problem. A descriptive type of normative juridical research used data collection techniques through library research. Secondary data was analyzed qualitatively. They are concluding using deductive logic. The research results show that the evidentiary power of land certificates can be broken by meeting minutes or organizational reports, even though the transfer of land rights is carried out without legal acts of sale and purchase. This will result in the transfer of rights being registered if the land is to be registered. The process of transferring rights or land certification must comply with applicable regulations. The judges did not consider aspects of formal evidence in handling case No.1333/Pdt.G/2021/PN.TngKeywords: Formal evidence, certificate of titles, authentic deed